2013
DOI: 10.14426/jsaa.v1i1-2.34
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of student affairs at Kenyan public universities

Abstract: Kenya is increasingly turning to the promise of mass higher education to help solve a range of economic and social issues. These efforts have had profound effects on university students, faculty and professionals who provide the vital student support services necessary for academic success. This case study explores the challenges that face Kenyan student services professionals within the context of the country's history and cultures. Kenya's student service professionals face four major challenges: the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The staff is unlikely to focus on the needs of students with disabilities when such students or their needs are not identified and particularly when the student : counsellor or welfare officer ratio is high. The findings compare with previous research which found that reliance on the Welfare Departments to support students and contribute to quality education is undermined by poor resourcing of such departments (Yakaboski & Birnbaum, 2013). Additionally, the university's deployment of academic staff to work as tutors without training them for the responsibility suggests it undermines the role of psychosocial support for student experience (Pansiri & Sinkamba, 2017).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The staff is unlikely to focus on the needs of students with disabilities when such students or their needs are not identified and particularly when the student : counsellor or welfare officer ratio is high. The findings compare with previous research which found that reliance on the Welfare Departments to support students and contribute to quality education is undermined by poor resourcing of such departments (Yakaboski & Birnbaum, 2013). Additionally, the university's deployment of academic staff to work as tutors without training them for the responsibility suggests it undermines the role of psychosocial support for student experience (Pansiri & Sinkamba, 2017).…”
Section: Discussioncontrasting
confidence: 38%
“…They could provide comprehensive co-curricular and extra-curricular services and programmes that address students' personal needs to enhance student experience (Pansiri & Sinkamba, 2017). However, Yakaboski and Birnbaum (2013) state that student affairs units at Kenyan higher education institutions are under-resourced and therefore deficient in providing required student experience.…”
Section: Introductionmentioning
confidence: 99%
“…Residence issues are a perennial problem for universities and frequently surface in demands by protesting students (Mugume & Luescher, 2015;Odundo et al, 2015;Yakaboski & Birnbaum, 2013). Students' demands have highlighted issues such as the poor management of residences, a lack of basic facilities, the distance of residences from teaching venues, and rules that compel students to remove their belongings during recess periods (Ajayi et al, 2015;Egwunyenga, 2009;Oke, Aigbavboa & Raphiri, 2017).…”
mentioning
confidence: 99%